Imam Shafi‘i - Carolyn Baugh (International Institute of Islamic Thought, 2013)
Kecia Ali has performed a great service for Islamic studies by harmonizing early sources with the most compelling recent scholarship to produce a biography of Muhammad ibn Idris al-Shafi‘i (d. 204/820), one of Islam’s most important figures. His life is presented in a tightly organized and lucid way, accessible to non-specialists or undergraduates, useful for graduate students, and a fine source of reference for scholars. This book consists of an introduction and six chapters. The first chapter covers his early years in Arabia, and the second discusses his transformation from “Student to Shaykh.” Chapters 3 through 5 present al-Shafi‘i’s legal theories and methodologies, and chapter 6, the final chapter, studies the popular cult that has grown up around him, thus delivering on the title’s promise. Also included are three pages of suggested “Further Reading,” along with why these works are pertinent, an invaluable extra measure that students will find particularly helpful. Needless to say, the bibliography is long and rich, giving a final affirmation to the author’s mastery of her subject. Throughout her study, Ali exhibits an acute awareness of the ideological agendas of the early biographers who have shaped perceptions of the imam. Her critical approach to traditional reports concerning his formative years (the oft-referenced Bedouin years, for example) allows her to question without discarding altogether some of the more famous episodes in his life. She ultimately suggests that what is most crucial for our understanding of al-Shafi‘i’s development was his encounter with Malik and his thought, an engagement so deep that he almost certainly had to have spent at least ten years under the elder scholar’s tutelage. These critical years laid the groundwork for the scholar he would become ...